Mental health risks and support for frontline workers during the 2013–2016 Ebola outbreak - Ira Chaturvedi; Andrew S. Huang; Amy Luo; Alexander H. Chang; J. Lee Jenkins; Edbert B. Hsu (Academia Mental Health & Well-Being)
The 2013–2016 West African Ebola virus outbreak was the longest and largest Ebola outbreak to date. High levels of stress and isolation experienced by frontline workers (FWs) during the Ebola outbreak highlight the importance of recognizing mental health and well-being (MHW). This study aimed to summarize and synthesize the MHW dimensions and interventions among FWs during the Ebola outbreak. A scoping review was conducted for English- and French-language articles indexed in PubMed and the Global Health Library, published from 2013 up to March 2025. Quantitative and qualitative studies reporting on the epidemiology and interventions for MHW among FWs, including healthcare personnel and ancillary health staff, during the Ebola outbreak were eligible for inclusion. A total of 22 articles were included in this review. Of these, 14 articles addressed the epidemiology of MHW for FWs, 3 addressed MHW interventions for FWs, and 5 addressed both topics. Studies interviewing FWs offered a glimpse into the unique psychological burden of responding to the outbreak, highlighting themes of stress, anxiety, social isolation, fear, and guilt. Intervention-based studies identified resources that could provide psychological support and/or relevant education. Recommendations aimed at the local, national, and international levels are proposed. Studies that address MHW among FWs during the Ebola outbreak are scarce, with even fewer describing interventions that address these issues. Demands on FWs remain an essential consideration during any emergent response, and further examination of impacts and interventions is needed.